Aerodynamics of ski jumping suits - Chowdhury, H.; Moria, H.; Alam, F.; Subic, A. (Sports Technology, 2011)
The primary purpose of this study is to understand the aerodynamic behaviour of textile fabrics used in ski jumping suits. Macro-scale (cylinder) and full-scale aerodynamic investigations of ski jumping suits and fabrics were undertaken. The aerodynamic effects of surface morphology of ski jumping fabrics were measured. On the basis of the macro-scale investigation, two full-scale ski jumping suits were developed and tested. The results from the macro-scale investigation show that the surface morphology affects the aerodynamic parameters (drag, lift and lift-to-drag ratio). The modified suit based on cylindrical test data shows 2.2% gain in lift-to-drag ratio, which can result in a difference in jump length of up to 4.44 m. The results also indicate that these effects can be utilised in ski jumping suit development to gain aerodynamic advantages. The analysed data from the full-scale investigation confirms the gain obtained from the macro-scale testing.